HUBUNGAN PENGETAHUAN GIZI IBU DENGAN PENERAPAN MENU 3B PADA ANAK BALITA DI JORONG SUNGAI SALAK KENAGARIAN KOTO TANGAH KECAMATAN TANJUNG EMAS KABUPATEN TANAH DATAR - RAHAYU, IFNALIA; Yusuf, Liswarti; Yuliana, Yuliana (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2014)
The problem in this study is still low maternal nutritional knowledge, there are many mothers who have not applied for a toddler menu 3B, the relationship with the mothers nutritional knowledge application menuÂ 3B in children under five. The purpose of this study was to describe maternal nutrition knowladge on food toddler, identify the application menu 3B for toddler, maternal, nutritional knowladge to analyze the reletionship with the application menu 3B in children under five. The reseach is ex post facto correlational nature. The population in this study were all housewives who have children under the age of 1-5 years districts in jorong sungai salak kenagarian koto tangah kecamatan tanjung emas kabupaten tanah datar 85 people. Samples numbered 50 persons obtained by simple random sampling. Data processed by descriptive and correlation with maternal nutrition knowledge application menu 3B in children under five. Result of research on maternal nutrition knowledge suggests that as many as 34% of mothers have the nutritional knowledge in the unfavorable category. The results of research on the application menu 3B show that as much as 32% application menu 3B in children under five in the unfavorable category. There is a significant correlation between maternal nutrition knowledge with the application menu 3B with correlation coefficient 0.287 and a significance value of 0.043. Â Keywords: Knowledge,nutrition, menu3B